Treatment of iron deficiency anemia with intravenous iron preparations - Akarsu, Saadet; Taskin, Erdal; Yilmaz, Erdal; Yilmaz, Huseyin; Kilic, Mehmet; Aygun, A. Denizmen (Karger, 2006)
Objective: We aimed to determine the effects of intravenous iron therapy on blood parameters in pediatric patients who do not tolerate oral iron therapy for any reason. Patients and Methods:The patient group consisted of candidates for elective operations requiring blood transfusions in order to raise hemoglobin (Hb) concentrations rapidly and for whom oral iron administration is useless and compliance with long-term treatment is definitely impossible due to sociocultural factors. Sixty-two children were included in the study. Venous blood samples were taken at diagnosis, and after 1 week and 1, 2 and 3 months. Hb, hematocrit, erythrocyte indices (mean erythrocyte volume, mean erythrocyte Hb and mean erythrocyte Hb concentration), serum iron (SI) levels, iron binding capacity, transferrin receptor (CD71) and serum ferritin levels were measured. Iron sucrose was used as an intravenous iron preparation. Results:All children showed improvements in iron deficiency anemia. A statistically significant elevation occurred between the time of diagnosis and week 1 (p < 0.05) in nearly all parameters. SI was raised until at least 1 month of therapy. There was no significant difference between transferrin receptors measured before and after the intravenous iron therapy. Ferritin did not exceed the values achieved in the 1st month. Mild side effects were encountered in only 8 (12.9%) patients. Treatment was not discontinued because of side effects in any case. The patients in the control group were given an oral form containing ferroglycine sulfate. Conclusion: Intravenous iron therapy can replace oral therapy in patients whose blood parameters must be raised rapidly and in situations where oral iron administration would not be appropriate for any reason. However, reinforcement with oral iron therapy or additional intravenous doses would be appropriate. Copyright (c) 2006 S. Karger AG, Basel
Keywords: iron deficiency anemia; parenteral treatment; intravenous treatment